Reconstructive complications and early toxicity in breast cancer patients treated with proton-based postmastectomy radiation therapy - Sayan, Mutlay; Hathout, Lara; Kilic, Sarah S.; Jan, Imraan; Gilles, Ambroise; Hassell, Natalie; Kowzun, Maria; George, Mridula; Potdevin, Lindsay; Kumar, Shicha; Sinkin, Jeremy; Agag, Richard; et al. (Frontiers in Oncology, 2023)
Background: Postmastectomy radiation therapy (PMRT) decreases the risk of locoregional recurrence and increases overall survival rates in patients with high-risk node positive breast cancer. While the number of breast cancer patients treated with proton-based PMRT has increased in recent years, there is limited data on the use of proton therapy in the postmastectomy with reconstruction setting. In this study, we compared acute toxicities and reconstructive complications in patients treated with proton-based and photon-based PMRT. Methods: A retrospective review of our institutional database was performed to identify breast cancer patients treated with mastectomy with implant or autologous reconstruction followed by PMRT from 2015 to 2020. Baseline clinical, disease, and treatment related factors were compared between the photon-based and proton-based PMRT groups. Early toxicity outcomes and reconstructive complications following PMRT were graded by the treating physician. Results: A total of 11 patients treated with proton-based PMRT and 26 patients treated with photon-based PMRT were included with a median follow-up of 7.4 months (range, 0.7-33 months). Six patients (55%) in the proton group had a history of breast cancer (3 ipsilateral and 3 contralateral) and received previous RT 38 months ago (median, range 7-85). There was no significant difference in mean PMRT (p = 0.064) and boost dose (p = 0.608) between the two groups. Grade 2 skin toxicity was the most common acute toxicity in both groups (55% and 73% in the proton and photon group, respectively) (p = 0.077). Three patients (27%) in the proton group developed grade 3 skin toxicity. No Grade 4 acute toxicity was reported in either group. Reconstructive complications occurred in 4 patients (36%) in the proton group and 8 patients (31%) in photon group (p = 0.946). Conclusions: Acute skin toxicity remains the most frequent adverse event in both proton- and photon-based PMRT. In our study, reconstructive complications were not significantly higher in patients treated with proton- versus photon-based PMRT. Longer follow-up is warranted to assess late toxicities.